Znaczenie pozycji wewnętrznej badacza w badaniach narracji osób należących do grupy mniejszościowej - Bandel, Jerzy (Człowiek i Społeczeństwo, 2023)
Insider research, i.e. research that the researcher conducts on a population, community, or identity group of which he or she is himself or herself a member, has been gaining popularity in psychological research in recent years. A subject of lively debate in the literature is the importance of the researcher’s characteristics shared with the research participant: life experiences, specific aspects of identity, traits, skills, or attitudes. This article summarises current knowledge on insider research and draws attention to the importance of analysing the psychologist researcher’s insider and outsider status. The article begins with an outline of the history of consideration of the importance of the researcher’s status in the social sciences and four main strategies for researchers to approach their insider status: minimizing and maximizing its importance, incorporating their experiences into the research material, and using them at different stages of the research process. Then, using the example of the author’s research project, it is shown how the last strategy can be applied during narrative research in planning the study, recruiting participants, conducting interviews, and analysing the data. The final part of the text is a consideration of the ethical dilemmas surrounding the conduct of insider research.